Answer:
63.44 feet
Step-by-step explanation:
tan(68 degrees)= 85/y
y tan (68 degrees)=85
y=85/tan(68 degrees) ( cross multiply)
y = 34.34 feet
tan (41 degrees)=85/x+y
(x+y)tan(41 degrees)=85
x+y=85/tan 41 degrees
x=85/tan(41 degrees) - y
x= 85/tan (41 degrees)-(34.34) (cross multiply)
Therefore, Travis stepped back 63.44 feet to gain a better view!
Answer:
from looking a the table we can see that hours is 4 and dollars is 72 so we divide 72/4=18 so one hour is 18 or on the graph
18,1
then we divide 162 by 18=9 on the graph
162,9
watch out this graph is by tens not ones
Hope This Helps!!!
Answer:
Alan = reject H0
Bill = cannot say
Step-by-step explanation:
Given that Heather is a student in a class that has been asked to conduct a hypothesis test for a population proportion.
![H0: p = 0.5 \\Ha: p ≠ 0.5](https://tex.z-dn.net/?f=H0%3A%20p%20%3D%200.5%20%5C%5CHa%3A%20p%20%E2%89%A0%200.5)
(two tailed test at 5% significance level)
Since she rejects null hypothesis p value should have been less than 0.05
when p value <0.05, it is definitely less than 0.10
So at 1% level of significance also the null hypothesis would be rejected.
So Alan also would get the same result as to reject the H0
But about Bill since Bill uses 0.01, we cannot definitely say that p value is less than or greater than 0.01
All we know is that p is less than 0.05
Hence it is impossible to tell from the information for Bill
9514 1404 393
Answer:
x = 10 2/3
Step-by-step explanation:
The ratios of corresponding sides are the same, so we have ...
x/8 = 8/6
x = 8·(8/6) = 64/6
x = 10 2/3
Answer: y = x/2 + 3
Step-by-step explanation:
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m = change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
Looking at the graph,
y2 = 6
y1 = 4
x2 = 6
x1 = 2
Slope,m = (6 - 4)/(6 - 2) = 2/4 = 1/2
To determine the intercept, we would substitute x = 2, y = 4 and m= 1/2 into y = mx + c. It becomes
4 = 1/2 × 2 + c
4 = 1 + c
c = 4 - 1
c = 3
The equation becomes
y = x/2 + 3